Law Enforcement in the Practice of Bribery in Business and Trade in Indonesia: Between Theory and Practice - Atikasari, Hartini; Amira, Btari; Arifin, Ridwan (UIN Sunan Kalijaga, 2020)
Abstract: Abuse of power for the sake of business and trade profit has become an increasingly average occurrence in the practice of public procurement in this era of moral disruption. It is commonplace that government officials make an illicit arrangement with companies through bribery scheme to win tenders in the procurement of goods and services. This practice resulted in a shift of ideology and abuse of authority by government officials. This practice is contrary to the professional code of ethics, so it is necessary to settle such cases through juridical channels. The intervention of public officials in determining the award of contracts of government projects to certain parties has resulted in a crisis of public trust in law enforcement in Indonesia. This article reviews the basic principles of the criminal act of corruption and the commitment and integrity of government officials in implementing the professional code of ethics, and upholding honesty in order to achieve equitable law enforcement. This paper proves and confirms that the abuse of power by government officials for the sake of business profit in the public procurement has weakened Indonesia’s investment sector. In many cases, these activities may even lead to unfair competition in the trade and business sectors.Abstrak: Memperdagangkan otoritas guna melancarkan praktik bisnis dan perdagangan merupakan hal yang banyak terjadi di era disrupsi moral ini. Para pejabat pemerintah sering kali bekerja sama dengan para pengusaha dengan cara membantu memberikan stimulus berupa kemenangan tender dalam pengadaan barang dan jasa. Praktik tersebut mengakibatkan terjadinya penyalahgunaan wewenang oleh para pejabat pemerintah. Hal ini bertentangan dengan kode etik profesi, sehingga diperlukan penyelesaian perkara melalui jalur yuridis. Adanya intervensi pejabat publik dalam penetapan pihak yang menangani proyek pemerintah menyebabkan terjadinya krisis kepercayaan publik terhadap penegakan hukum di Indonesia. Artikel ini menelaah ulang dasar pokok aturan-aturan tentang tindak pidana korupsi serta bagaimana komitmen dan integritas para pejabat pemerintah dalam melaksanakan kode etik profesi, menjunjung tinggi kejujuran guna mewujudkan penegakan hukum yang adil. Tulisan ini membuktikan dan menegaskan bahwa perdagangan otoritas dalam praktik bisnis melemahkan sektor investasi Indonesia. Pada banyak kasus, kegiatan ini bahkan cenderung memperkuat kondisi persaingan tidak sehat dalam sektor perdagangan dan bisnis.